(untitled) (Proceedings of the International Conference on Poverty and Sustainable Development, 2018)
1977 is the year which it introduced open economy to Sri Lanka and as result not only men but also women who became the breadwinner of a family. The women or men, who live in rural areas and fell in poverty, select migration as the oldest action against poverty. The sample survey was conducted in Sri Lanka from August to December 2017, covering 80 females who were worked so domestic human resources abroad. The study explore the bond sandwiched between the poverty furthermore the migration of the special analysis area in Sri Lanka. Sri Lanka has paid attention to overcome the problem of poverty since her independence, but still there are considerable amount of the population living below the national poverty line. Also relevant data for the study were gathered from the secondary as well as primary sources. The main primary data collection methods were questionnaire survey, household interviews and key informant interviews. The present situation of the village is a result of number of factors which directly or indirectly affect the women’s and men’s economy in Sri Lanka. The study found that the main reason for their poverty situation is low income regarding the lack of educational attainment of the women have negatively affected their present living standard. And also most of the women reported that present poverty alleviation program (Samurdhi) isn’t enough to overcome the poverty situation. Other reasons for women’s migration were image the relationship of present poverty situation in the area, lost some valuable opportunities for their education due to poor condition of their families, thinking much about their children and fulfill their requirements than others requirements of the households’ etc. It seems that there is no good guidance for the poor people of the area. As many of the people in the village have the negative ideas about their poverty situation, there should be stronger guidance for the people. Without such a strengthening of the people it is difficult to upgrade peoples’ living standard. If there is awareness programs and if give some kinds of training and self-employment programs, it will be helpful to overcome their poverty conditions and not to get decision to migrate.